Und es bewegt sich doch... : Von Alexander Calder und Jean Tinguely bis zur zeitgenössischen "mobilen Kunst". - Wick, Oliver; Golinski, Hans Günter; Stahlhut, Heinz; Geisel, Sieglinde; Roth, Carsten; Hiekisch-Picard, Sepp; Kivelitz, Christoph; Becker, Regina; Zeising, Andreas; Schmidt, Andrea; Schamp, Matthias; Museum Bochum (Bochum : Museum Bochum, 2006)
Zins, Günther ; Zieschang, Kim ; Wilken, Frauke ; von Huene, Stephan ; Vaara, Roi ; Ufan, Lee ; Uecker, Günther ; Tinguely, Jean ; Takeuchi, Takakazu ; Sudhues, Max ; Spagnulo, Giuseppe ; Signer, Roman ; Schweppe, Awel ; et al.
Museum Bochum, 11.06.2006 - 03.09.2006
Max Sudhues (.)
kunstcatalogus